An enhanced fluorescence detection of a nitroaromatic compound using bacteria embedded in porous poly lactic-co-glycolic acid microbeads. Issue 14 (24th June 2021) - Qiao, Tian; Kim, Soohyun; Lee, Wonmok; Lee, Hyunjung
Abstract : The enhanced sensing performance of green fluorescence protein-based sensor for the nitroaromatic compound detection. Abstract : The detection of explosive nitroaromatic compounds has caused worldwide concern for human safety. In this study, we introduce a fluorescent biosensor based on porous biocompatible microspheres loaded with a bioreporter for the detection of nitroaromatic compounds. Poly(lactic- co -glycolic acid) microbeads were designed as biosensors embedded with the bacterial bioreporters. The genetically engineered bacterial bioreporter can express a green fluorescent protein in response to nitroaromatic compounds ( e.g., trinitrotoluene and dinitrotoluene). The modified surface structure in microbeads provides a large surface area, as well as easy penetration, and increases the number of attached bioreporters for enhanced fluorescent signals of biosensors. Moreover, the addition of the M13 bacteriophage in open porous microbeads significantly amplified the fluorescence signal for detection by the π–π interaction between peptides in the M13 bacteriophage and nitroaromatic compounds. The modification of the surface morphology, as well as the genetically engineered M13 phage, significantly amplifies the fluorescence signal, which makes the detection of explosives easier, and has great potential for the stand-off remote sensing of TNT buried in the field.